Computed Tomography (CBCT) Services by Product Quality, Customer Trust and Customer Loyalty: A Linear Regression - Rizki Rizki; Rian Adi Pamungkas; Wahyuni Dian Purwati (International Journal of Nursing and Health Services (IJNHS), 2021)
Introduction: In a hospital service, there must be a superior service that can be used as a weapon in capturing patients in carrying out treatment through doctor referrals, in this case the presence of CBCT services. Word of Mouth (WOM) occurs when customers talk to others about their opinion about a particular brand, product, service or company to others. There are several factors that are believed to increase the desire of a referring dentist to do word of mouth, including the quality of the CBCT product itself, loyalty and the level of trust of a dentist as a consumer. Objective: The study aimed to examine the relationship between product quality, customer trust, and customer loyalty with word of mouth on CBCT services. Method: The descriptive study was undergone with cross-sectional approach. A total of 134 dentists as were selected using the systematic random sampling. The linear regression was used to analyze the data to test between the dependent and independent variables. Results: The findings showed that there are significantly associated between the product quality, customer trust, and customer loyalty to word of mouth of customer for using the CBCT services. Recommendation: Further researchers need to develop path analysis or SEM methods to predict the word of mouth of customer for using the CBCT services